2019
DOI: 10.1136/bjophthalmol-2019-315020
|View full text |Cite
|
Sign up to set email alerts
|

MRI of posterior eye shape and its associations with myopia and ethnicity

Abstract: PurposeTo evaluate posterior eye shape variations across a wide refractive error range using brain MRI in a multiethnic cohort.MethodsAdult subjects in the multiethnic Singapore Epidemiology of Eye Disease study were included. Spherical equivalent (SE) was measured using subjective refraction, and axial length (AL) was measured using optical biometry. MRI was performed using a 3-Tesla whole body scanner with a 32-channel head coil. The radii and asphericity based on fitting of the posterior two-thirds of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…A more hyperopic relative peripheral refraction in both the horizontal and vertical retina was observed in the high myopic eyes compared to the emmetropic eyes, which is consistent with the previous studies [10,28]. Peripheral hyperopic refraction is considered to be responsible for myopia development in a number of animal models.…”
Section: Discussionsupporting
confidence: 91%
“…A more hyperopic relative peripheral refraction in both the horizontal and vertical retina was observed in the high myopic eyes compared to the emmetropic eyes, which is consistent with the previous studies [10,28]. Peripheral hyperopic refraction is considered to be responsible for myopia development in a number of animal models.…”
Section: Discussionsupporting
confidence: 91%
“…Verkicharla et al 32 have reported that east Asians had steeper retinas than Caucasians, which might be related to more positive RPR. Lim et al 33 also found that Chinese eyes have fewer oblate shapes than Malay and Indian eyes, especially in non-myopic eyes.…”
Section: Discussionmentioning
confidence: 96%
“…Further, the presence of offset rendered demarcation of the LC insertion margin more complicated. Third, all of the participants were South Korean, and there may be ethnic differences in ONH morphology 35 . Further research may be required to validate the current ndings for different populations.…”
Section: Discussionmentioning
confidence: 99%